Exploring the methodology of Da’wah: The prophetic model and its relevance to the contemporary era - Dr. Muhammad Hammad; Laraib Zahid; Rabia Unber Malik; Dr. Abdul baqi; Neelam Shad (Al-Qanṭara, 2024)
Islam is a peaceful religion that teaches love, sincerity, and brotherhood to all mankind. Propagating Islam by beneficial means is called Da'wah and is one of the strategies favored by the Holy Prophet (SAW) to spread Islam. He adopted a new and better strategy and, in a short time the light of Islam has spread throughout the world. This study applies a qualitative methodology to examine Quranic verses, Hadiths, scholarly interpretations, and historical accounts in order to identify the main ideas and methods of Da'wah that Prophet Muhammad (SAW) used. The study also includes analysing the prophetic strategies, and educational aspects, highlighting how flexible it is for contemporary situations. Firstly, the current study shares valuable knowledge on prophetic Da'wah methodology and highlights the importance of Da'wah in everyday life with relevant examples. Secondly, this research is primarily focused on the Divine Prophet's Da'wah strategy to be addressed and implemented in the 21st century. Moreover, the life of the Holy Prophet (SAW) is a great source of learning and his Da'wah techniques must be learned and embraced as preaching Islam. It’s the duty of every Muslim man and woman. This treatise offers immense knowledge of the Prophetic Da'wah techniques that are fruitful examples for all mankind. Finally, this paper concludes that these Da’wah principles are useful and desirable not only for Muslim-non-Muslim relations, but also for improving and maintaining Muslim-Muslim relations.